The Influence of Content Marketing, Viral Marketing and Influencers on Repurchase Intention and Customer Satisfaction: (Case Study on Monsieur Spoon Bakery) - Nopridawati; Usep Suhud; Osly Usman (MultiTech Publisher, 2024)
This study aims to determine the effect content marketing, viral marketing, influencers on repurchase intention and customer satisfaction at Monsieur Spoon which is one of the first Bakery stores that sell Cromboloni in Indonesia, especially in Bali and Jakarta. The population of this study was 163 thousand, with a sample of 200 people. The data collection method uses a questionnaire distributed to 200 respondents from Monsieur Spoon's Instagram followers with the criteria of Monsieur Spoon's Instagram followers, who had bought Monsieur Spoon cromboloni. The analysis technique used in this study is the Structural Equation Model (SEM) with the help of the SmartPLS (Analysis Partial Least Square) program. The results of the study concluded that there is a positive and significant effect of content marketing, viral marketing,content marketing, viral marketing, infleuncers have a positive and significant effect on customer satisfaction. And there is a positive and significant influence of customer satisfaction on repurchase intention